2019
DOI: 10.21608/ejh.2019.16398.1159
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Spirulina on Propylthiouracil - Induced Hypothyroidism in Albino Rats, a histological, immunohistochemical and biochemical approach

Abstract: Background: Hypothyroidism is a decrease in the production of the thyroid hormones and leads to gland dysfunction. Spirulina used as an antioxidant and supposed as antihypothyroidic agent. Objective: This study was carried out to investigate the impact of Spirulina on PTU-induced hypothyroidism in rats. Materials and Methods: The rats were divided into six groups, control group (G1), hypothyroid group (G2), SP-500 treated group (G3), SP-1000 treated group (G4), PTU+SP-500 treated group (G5) and PTU+SP-1000 tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…In this study, CV treatment with 300 mg/kg for 30 days revealed a rebalance through TSH elevation besides decreased level of T3 and T4 in ACR-induced toxicity groups. Our results are clearly in line with previous study of [57][58][59] who all indicated similar results after treatment with different doses of Spirulina. A considerable imbalance between the activity of peroxidation processes and the antioxidant defense system was obvious in thyroid tissue [60].…”
Section: Groupssupporting
confidence: 93%
“…In this study, CV treatment with 300 mg/kg for 30 days revealed a rebalance through TSH elevation besides decreased level of T3 and T4 in ACR-induced toxicity groups. Our results are clearly in line with previous study of [57][58][59] who all indicated similar results after treatment with different doses of Spirulina. A considerable imbalance between the activity of peroxidation processes and the antioxidant defense system was obvious in thyroid tissue [60].…”
Section: Groupssupporting
confidence: 93%
“…On the other hand, we observed higher locomotor activity during the first minute of the open field test, this might be due to greater anxiety level and, as a result, prominent escape behavior during the initial minutes of the test [24]. These findings significantly support the concept that appropriate thyroid hormones in early postnatal life are vital to the development of the central nervous system, which is required for emotion and motor control [27]. The relationship between thyroid hormone abnormalities, particularly early hypothyroidism, and alterations in anxiety-related behaviors is widely documented but not entirely understood [35].…”
Section: Discussionsupporting
confidence: 78%
“…This decrease could be attributed to the decline in levels of T3 and T4 that have a potential effect on the metabolism and homeostasis in animal body. Also, certain study referred to the previous result of impairment in energy metabolic processes along with a decrease in the basal metabolic rate [27]. On another hand, it would seem that the drug's more direct impact on the adrenal cortex is what is causing these alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Group I-b (positive control): Four rats received spirulina (500 mg/kg) body weight orally by using a gastric tube for 8 days (18) . Group II (cisplatin-treated group): The animals were administrated a single dose of cisplatin 6 mg/kg body weight intraperitoneal (19) .…”
Section: Ethical Considerationmentioning
confidence: 99%